2014
DOI: 10.5114/aoms.2014.44855
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review/Meta-analysis Clinical outcomes of second- versus first-generation drug-eluting stents in patients with acute myocardial infarction: a meta-analysis of randomized controlled trials

Abstract: IntroductionIt remains unclear whether the clinical outcomes of patients with acute myocardial infarction (AMI) receiving second- and first-generation drug-eluting stents (DES) are identical. The study aimed to investigate the differences in clinical utility between the two generations of DES in these specific subjects by a meta-analysis.Material and methodsWe systemically searched PubMed and EMBASE databases and the Cochrane Library up until January 2013. Randomized trials, which compared clinical outcomes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Studies have confirmed that second-generation DES is more beneficial than first-generation DES 3 5 as it reduced the late ST risk. Therefore, it is reasonable to shorten the DAPT duration after second-generation DES implantation.…”
Section: Introductionmentioning
confidence: 95%
“…Studies have confirmed that second-generation DES is more beneficial than first-generation DES 3 5 as it reduced the late ST risk. Therefore, it is reasonable to shorten the DAPT duration after second-generation DES implantation.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, every effort is being made to improve not only therapy but also risk stratification. Novel parameters helpful in the assessment of prognosis are continuously searched for [3133]. High-risk patients require more intensive ambulatory monitoring and more aggressive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 26 27 ] Some studies even demonstrated remarkably lower long-term mortality with second-generation DES as compared with first-generation DES. [ 28 29 30 ] Presently, second-generation DES were widely applied in patients with CAD undergoing PCI in clinical practice. With the exception of the EXCEL study,[ 23 ] all other previous studies[ 21 22 24 ] have enrolled patients entirely or mostly treated with first-generation DES.…”
Section: Discussionmentioning
confidence: 99%